Transformasi Paradigma Filsafat Hukum di Era Kecerdasan Buatan: Analisis Filosofis atas Legitimasi, Akuntabilitas, dan Keadilan Yurisprudensi Berbasis AI di Indonesia (Studi Kasus Implementasi Sistem Analisis Putusan di Universitas Muhammadiyah Malang) - Mirza Athaya Ghaisan Hakeem (Media Hukum Indonesia (MHI), 2026)
The development of Artificial Intelligence (AI) has brought significant transformations to judicial processes, particularly in legal analysis and decision-making. This study aims to analyze how the legitimacy of AI-assisted jurisprudence can be maintained, how the accountability and fairness of AI-influenced court decisions can be ensured, and the implications for contemporary legal philosophy in Indonesia. The research employs a contemporary legal philosophy approach, combining normative, theoretical, and empirical analyses, focusing on the case study of the Retrieval-Augmented Generation (RAG) system implementation at Universitas Muhammadiyah Malang (UMM), which analyzed 408 court decisions related to human trafficking crimes (TPPO). The results indicate that jurisprudential legitimacy can be preserved if final decisions remain under the authority of judges, while AI serves as a tool to enhance efficiency, consistency, and decision accuracy. Accountability is maintained through algorithm audits, transparency, and human oversight, whereas substantive justice requires human consideration of social, cultural, and moral contexts. These findings highlight a paradigm shift in Indonesian legal philosophy toward a hybrid model integrating technology with human ethical-legal judgment, while preserving the integrity, morality, and legitimacy of jurisprudence. This study is expected to serve as a reference for developing regulations and AI applications in the Indonesian legal system.